2018
DOI: 10.1242/jcs.208447
|View full text |Cite
|
Sign up to set email alerts
|

Chemical signaling for pollen tube guidance at a glance

Abstract: Pollen tube guidance is a unique navigating system that is required for the successful sexual reproduction of plants. As plant sperm cells are non-motile and egg cells are embedded deep inside the female tissues, a pollen tube delivers the two sperm cells that it contains by growing towards the ovule, in which the egg cell resides. Pollen tube growth towards the ovule is precisely controlled and divided into two stages, preovular and ovular guidance. In this Cell Science at a Glance article and accompanying po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 113 publications
(142 reference statements)
1
51
0
Order By: Relevance
“…In the amp1 mutant, 19% of the ovules showed EC1.1pro∷HTA6–3GFP expression in both synergid cells, whereas 26% of the ovules showed their expression in only one of the synergid cells (notably, 45% of the ovules have no detectable fluorescent signal) (Kong et al, 2015). The synergid cells play an important role in the pollen tube attraction, by secreting peptides (Mizuta and Higashiyama, 2018). Previously, we found that the laser disruption of the immature egg cells affects the cell differentiation for one of the synergid cells in the Torenia fournieri (Susaki et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the amp1 mutant, 19% of the ovules showed EC1.1pro∷HTA6–3GFP expression in both synergid cells, whereas 26% of the ovules showed their expression in only one of the synergid cells (notably, 45% of the ovules have no detectable fluorescent signal) (Kong et al, 2015). The synergid cells play an important role in the pollen tube attraction, by secreting peptides (Mizuta and Higashiyama, 2018). Previously, we found that the laser disruption of the immature egg cells affects the cell differentiation for one of the synergid cells in the Torenia fournieri (Susaki et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been proposed to explain the precise growth of pollen tubes towards the ovules, including mechanical, chemotropic and physiological guidance cues (reviewed by Mizuta & Higashiyama, ). Our findings are consistent with an important role of DGK proteins in pollen tube growth and of DGK4 in tube guidance acting as a link between signalling pathways and secretion of cell wall material.…”
Section: Discussionmentioning
confidence: 99%
“…Fertilization is a key process for sexual reproduction, and an important point in this process is that the pollen tubes can reach the ovules. The synergid cells, in the embryo sac inside the ovule, produce signals to attract the pollen tube (Mizuta and Higashiyama, 2018). For pollen tubes to reach the ovules, cell wall modifications have to take place (Crawford and Yanofsky, 2008;Dresselhaus and Franklin-Tong, 2013).…”
Section: Introductionmentioning
confidence: 99%